Automation in the Era of Economic Crises. Issue 1 (2nd April 2016) - Mather, Yassamine
Abstract : As the world economy faces yet another downturn we hear on the one hand a lot of hype about the role of new technology in saving the economy and on the other hand fears expressed about robots and artificial intelligence replacing humans. This article is an attempt at explaining the challenges faced by new technology and the current state of automation and computing as well as the consequences of such development on civil rights.